Electrochemical metallization cell with anion supplying active electrode - Ziyang Zhang (Nature Portfolio, 2018)
Abstract Electrochemical metallization (ECM) memories are among the various emerging non-volatile memory technologies, contending to replace DRAM and Flash and enabling novel neuromorphic computing applications. Typically, the operation of ECM cell is based on the electrochemical redox reactions of the cation supplying active electrode (e.g., Ag, Cu). Although extensively investigated, the possibility of utilizing new materials for the active electrode remains largely undiscussed. In this paper, an ECM cell with a Te active electrode is fabricated. It is found that the SET operation of the device occurs under negative voltage on the active electrode, which is opposite to that of the device with Ag electrode, indicating that the Te electrode supplies Te2− anions by electrochemical reduction. The influence of the electrolyte material on the switching properties is also found to be more significant for devices with Te electrodes. For Pt/GeS/Te and Pt/Ge2Sb2Te5/Te cells, repeatable unipolar and bipolar resistive switching are observed, respectively, which can be attributed to the rupture of the filament by Joule heating for the former and by ECM for the latter in the RESET process. The semiconducting properties of Te, the reversed operating polarity and the electrolyte dependent switching characteristics open up unprecedented prospects for ECM cells.